The Effects of Financial Literacy and Self-Control towards Financial Behavior among High School Students in Bogor - Jihaan Khoirunnisaa; Irni Rahmayani Johan (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2020)
This research aims to analyze the effect of financial literacy and self-control on financial behavior among Bogor High School students. This research was conducted in two public high schools in Bogor, West Java, Indonesia, that were selected based on the level of passing grade of the school (high-grade and low grade). In collecting the data, this study used a self-administered questionnaire. About 113 of senior high school students from science and social majors were selected as the sample. This study found that financial knowledge and financial attitude were on a moderate level. High-grade school students tend to have better financial knowledge and attitude than those from low-grade schools. The results of this study also show that the self-control of students was classified as a low category. Those from low-grade schools were more likely to have better self-control compared to students from the high-grade school. Furthermore, financial behavior, which consists of saving and spending behavior, were categorized as poor. There was a significant difference in financial knowledge, financial attitude, and self-control among both schools. The financial attitude was positively significantly related to financial knowledge and behavior. Self-control was associated positively with financial behavior. Further analysis of multiple linear regression shows a positive and significant effect of financial attitude and self-control towards financial behavior.